2020
DOI: 10.1007/s10853-020-04814-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curing conditions on the water vapor sorption behavior of melamine formaldehyde resin and resin-modified wood

Abstract: Impregnation modification of wood with melamine formaldehyde resin reduces the adverse effects caused by moisture uptake, but the underlying modes of action are not fully understood. The present study showed that it is crucial to understand the sorption behavior of the pure resin when interpreting the behavior of resin-modified wood. Furthermore, the applied heat-curing conditions had a significant effect on the moisture uptake of resin-modified wood. At the same resin loads, dry curing conditions were more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Solid wood blocks were milled in a cutting mill (RETSCH SM 2000, Retsch GmbH, Haan, Germany) to pass through a 2 mm mesh screen. Hydrogendeuterium exchange (HDX) was performed in a dynamic vapor sorption (DVS) apparatus (DVS ET, Surface measurement Systems, London, UK) as described previously [18]. In short, approximately 20 mg of wood particles were first dried using the pre-heater at 60°C for 6 h under dry nitrogen flow (0% RH) followed by a temperature stabilization period to 25°C for 2 h. The particles were then exposed to deuterium oxide (D 2 O) vapor at a target RH of 95% for 12 h. Finally, the dry mass was determined again as described above.…”
Section: Hydrogen -Deuterium Exchangementioning
confidence: 99%
See 3 more Smart Citations
“…Solid wood blocks were milled in a cutting mill (RETSCH SM 2000, Retsch GmbH, Haan, Germany) to pass through a 2 mm mesh screen. Hydrogendeuterium exchange (HDX) was performed in a dynamic vapor sorption (DVS) apparatus (DVS ET, Surface measurement Systems, London, UK) as described previously [18]. In short, approximately 20 mg of wood particles were first dried using the pre-heater at 60°C for 6 h under dry nitrogen flow (0% RH) followed by a temperature stabilization period to 25°C for 2 h. The particles were then exposed to deuterium oxide (D 2 O) vapor at a target RH of 95% for 12 h. Finally, the dry mass was determined again as described above.…”
Section: Hydrogen -Deuterium Exchangementioning
confidence: 99%
“…All measurements were done in triplicate. The amount of exchanged H and the amount of absorbed D 2 O (both in mmol g -1 ) was calculated as described by [18] using either the dry specimen mass or the dry wood mass (excluding the mass of the added resin) as the reference mass for the calculations.…”
Section: Hydrogen -Deuterium Exchangementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that the amount of absorbed water can change independently from the OH accessibility (Stevens and Smith 1970;Rautkari et al 2013;Salmén and Stevanic 2018). There is evidence that additional factors have a strong impact on the amount of absorbed water without affecting the sorption site density, such as the degree of crosslinking in heat-treated wood (Altgen et al 2018;Willems et al 2020) or the spatial availability of wood cell walls in modified wood (Thybring et al 2020;Altgen et al 2020). Furthermore, Lindh et al (2016) showed that OH(3) groups in cellulose that are associated with the C(3) atom of the glucose units are unreactive to H-D exchange, but these OH groups may still form hydrogen bonds with water molecules.…”
Section: Introductionmentioning
confidence: 99%